COMPARATIVE PROXIMATE ANALYSIS OF SOME DATE PALM CULTIVARS (Phoenix dactylifera l.) (FUDMA JOURNAL OF SCIENCES, 2023)
Comparative proximate analyses of five samples of date palm cultivars Phoenix dactylifera were carried out. The experimental was laid on Complete Randomized Design (CRD) with three replications on each sample.The fleshes were separated from the seeds, rinsed with distilled water and dried for 24 h at 40°C. Proximate analysis, mineral composition and vitamin C content of the fruit flesh were evaluated. Moisture and ash contents were determined using oven drying method, crude protein (Kjeldahl method), crude fat (dry extraction), fibre (acid-alkaline digestion), sugar (phenol-sulphuric acid), calcium and magnesium (atomic absorption spectrometry), sodium (Flame photometry) and vitamin C using dichlorophenol-indophenol. The result of the analysis shows that sucker seed garden had the highest amount of fibre (2.17g/100g), crude fat (0.59g/100g), and Magnesium content (2482.42mg/kg). F4 R16 GPIII had the highest amount of crude protein (3.45g/100g), sugar (79.40%), and Calcium content (13012.43mg/kg). Based on the analyses conducted, it was concluded that sucker seed garden and F4 R16GPIII had the highest nutritional contents in most of the nutrients assessed. It was also observed that, date palm contains many minerals in the fruit such as sodium, potassium, calcium and magnesium in considerable amount. However, it was also seen that the different cultivars of dates contain different amount of nutrient. Antioxidants and phytochemicals analyses of this fruit are suggested to be carried out, to reveal the bioactive compounds present and proper research on medicinal and health benefit comparing different varieties of date palm is encouraged to be studied.
Keywords: Date palm, Proximate analysis, Minerals, Sucker seed garden, oven drying.